Pengaruh Latihan Range Of Motion (ROM) Menggenggam Bola Terhadap Kekuatan Otot Ekstremitas Atas Pasien Stroke Iskemik - Hendri Budi; Netti Netti; Yossi Suryarinilsih (Poltekkes Kemenkes Padang, 2019)
Stroke causes motor hemiparise disorders or weakness. Nursing intervention to overcome this is by doing range of motion (ROM) exercises grasping the ball. The purpose of the study was to identify the effect of ROM-grasping ball exercises on the strength of limb muscles for ischemic stroke patients. Quasi-experimental research type, one group pre-post test design. Research in the Neuro Ward Dr. M. Djamil Padang Hospital. The time of the research is October to December 2017. The intervention is ROM gripping ball exercises, namely rubber balls for 3 days followed by tennis balls for 2 days. Hold the ball firmly for 5 seconds then relax 10 seconds, practice repeated 10 times, frequency 3 times a day. The study population were all stroke patients in the Neuro Ward Dr. M. Djamil Padang Hospital. A sample of 10 people was obtained by purposive sampling that met the inclusion criteria. Data collection by measurement of muscle strength using Manual Muscle Testing (MMT). Data were computerized, analyzed by descriptive statistics and Wilcoxon test. The results of the study showed differences in upper limb muscle strength before and after the ROM exercise held the ball on the patient's shoulder (p value = 0.004), on the elbow of the patient (p value = 0.000), on the patient's hand (p value = 0.000), and on the patient's finger (p value = 0.000). It is recommended to nurses to implement the practice of grasping the ball to increase muscle strength of ischemic stroke patients and make it as a procedure for nursing intervention to patients to muscle strength.